Spinal Schwannomas: A Proposal for a New Classification to Aid Surgical Planning - Aydın, Serdar Onur; Etli, Mustafa Umut; Sarıkaya, Caner; Köylü, Reha Can; Varol, Eyüp; Ramazanoğlu, Ali Fatih; Yaltırık, Cumhur Kaan; Şerifoğlu, Luay; Kayalar, Ali Erhan; Naderi, Sait (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
The current standard of care for spinal schwannoma, which is the most common nerve sheath tumor, is total microsurgical resection. The localization, size, and relationship with the surrounding structures of these tumors are crucial in terms of preoperative planning. A new classification method for surgical planning of spinal schwannomas is presented in this study.All patients who underwent surgery for spinal schwannoma between 2008 and 2021 were reviewed retrospectively, along with radiologic images, clinical presentation, surgical approach, and postoperative neurologic status.A total of 114 patients (57 males and 57 females) were included in the study. Tumor localizations were cervical in 24 patients, cervicothoracic in 1 patient, thoracic in 15 patients, thoracolumbar in 8 patients, lumbar in 56 patients, lumbosacral in 2 patients, and sacral in 8 patients. All tumors were divided into seven types according to our classification method. Type 1 and 2 groups were operated on with a posterior midline approach only, type 3 tumors were operated on with a posterior midline approach and an extraforaminal approach, and type 4 tumors were operated on with only an extraforaminal approach. While the extraforaminal approach was sufficient in patients with type 5 tumors, partial facetectomy was required in 2 patients. A combined surgery including hemilaminectomy and extraforaminal approach was performed in the type 6 group. A posterior midline approach with partial sacrectomy/corpectomy was performed in the type 7 group.Effective treatment of spinal schwannoma depends on preoperative planning, which includes correctly classifying tumors. In this study, we present a categorization scheme that covers bone erosion and tumor volume for all spinal localizations.
Keywords: spinal; schwannoma; approach; classification